ANALISIS EFISIENSI KINARJA ECONOMIZER DI PT. PLN (PERSERO) KALIMANTAN SELATAN-TENGAH SEKTOR PLTU ASAM – ASAM - Abdul Gapur; Aqli Mursadin (JTAM ROTARY, 2019)
Electrical energy is the dominant energy needed for human life. One source of electricity income is Steam Power Plant (PLTU). With an installed capacity of     4 x65 MW for public transportation, each unit of acid acid plant has one boiler with 1 economizer as a means of boiler efficiency enhancer by absorbing hot flue gas. To avoid it then in need of maximum care to components of economizer. To see the effectiveness of the economizer it is necessary to observe the economizer. This study aims to analyze the effectiveness of the economizer. From the results of the boiler efficiency study from March 27, 2017 to April 10, 2017 with a total average efficiency in the analysis of 81.93%. With the highest efficiency on date On March 29, 2017 the efficiency calculated was 83.42% at 02:00. And the lowest on April 2, 2017, an 80.32% efficiency at 09:00. The factor that influences the efficiency ratio is the temperature difference between the incoming gas gas furnace (T_ (h, i)), exit (T_ (h, o)) and the feed water inlet tube temperature       (T_ (c, i)). The research obtained the highest heat transfer coefficient that is equal to 1.647,1 Btu/h.ft2 at 227,4°C on 27/03/2017 and the lowest that is equal to 1.636,91 Btu/h.ft2 at 233°C on 28/03/2017 Keywords: Economizer, Feed Water Tube, Flue Gas, Koefisien Heat Transfer, Heat transfer